Clinicopathological profile of colorectal carcinoma in a tertiary care teaching hospital in Pokhara, Nepal - Bhattarai, Subash; Karki, Om Bahadur; Gyawali, Merina; Regmi, Sudeep (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Colorectal cancer is the most common malignancy of the gastrointestinal tract. They are common after 50 years of age and present with bleeding per rectum, altered bowel habits, anemia, pain abdomen, and weight loss. The objective of this study was to evaluate the demographic profile, clinical presentation, colonoscopy and histopathology findings of colorectal cancer. Methods: A descriptive cross-sectional study was conducted. Cases were studied from the departmental records. Clinical presentation, CT abdomen, colonoscopy, and histopathology findings of colorectal carcinoma were studied. Data entry was done in SPSS version 20. Results: The mean age of subjects was 56 ± 11.42 years (range of 34 – 80 years) with male predominance (M: F=3:2). Changes in bowel habits (92.3%), chronic abdominal pain (84.6%), generalized weakness (80.7%), rectal bleeding (46.2%), and significant weight loss (42.3%) were the most common presenting symptoms. Rectal carcinoma was the most common (35%) followed by carcinomas of ascending colon (14%) and descending colon (10 %). The most common morphology was proliferative growth (61.5%). All colorectal carcinomas were adenocarcinoma, and the majority was moderately differentiated (51.9%). Conclusion: Colorectal cancers are seen above 50 years of age and common in males. Changes in bowel habits, chronic abdominal pain, generalized weakness, rectal bleeding, and weight loss are the most common form of presentations. These patients usually present late with advanced disease and unfavorable histopathology. Screening colonoscopy >50 years is strongly recommended.